Automated grindstone chemistry: a simple and facile way for PEG-assisted stoichiometry-controlled halogenation of phenols and anilines using N-halosuccinimides - Das, Dharmendra; Bhosle, Akhil A.; Chatterjee, Amrita; Banerjee, Mainak (Beilstein Journal of Organic Chemistry, 2022)
A simple electrical mortar–pestle was used for the development of a green and facile mechanochemical route for the catalyst-free halogenation of phenols and anilines via liquid-assisted grinding using PEG-400 as the grinding auxiliary. A series of mono-, di-, and tri-halogenated phenols and anilines was synthesized in good to excellent yields within 10–15 min in a chemoselective manner by controlling the stoichiometry of N-halosuccinimides (NXS, X = Br, I, and Cl). It was observed that PEG-400 plays a key role in controlling the reactivity of the substrates and to afford better regioselectivity. Almost exclusive para-selectivity was observed for the aromatic substrates with free o- and p-positions for mono- and dihalogenations. As known, the decarboxylation (or desulfonation) was observed in the case of salicylic acids and anthranilic acids (or sulfanilic acids) leading to 2,4,6-trihalogenated products when 3 equiv of NXS was used. Simple instrumentation, metal-free approach, cost-effectiveness, atom economy, short reaction time, and mild reaction conditions are a few noticeable merits of this environmentally sustainable mechanochemical protocol.
Keywords: automated grinding; chemoselectivity; mechanochemistry; N-bromosuccinimide; PEG-400; regioselectivity; stoichiometry-controlled halogenation

Organic Bromine and Iodine Compounds - Neilson, A. H. (Springer, 2003)

(untitled) - Öztaşkın, N.; Çetinkaya, Y.; Taslimi, P.; Göksu, S.; Gülçin, İ. (Bioorg. Chem., 2015)

(untitled) - Liu, M.; Hansen, P. E.; Lin, X. (Mar. Drugs, 2011)

(untitled) - Jesus, A.; Correia-da-Silva, M.; Afonso, C.; Pinto, M.; Cidade, H. (Mar. Drugs, 2019)

(untitled) - Gribble, G. W. (J. Chem. Educ., 2004)

(untitled) - Ruiz-Castillo, P.; Buchwald, S. L. (Chem. Rev., 2016)

(untitled) - Sun, C.-L.; Shi, Z.-J. (Chem. Rev., 2014)

(untitled) - Tellis, J. C.; Kelly, C. B.; Primer, D. N.; Jouffroy, M.; Patel, N. R.; Molander, G. A. (Acc. Chem. Res., 2016)

(untitled) - Weix, D. J. (Acc. Chem. Res., 2015)

(untitled) - Tabassum, S.; Zahoor, A. F.; Ahmad, S.; Noreen, R.; Khan, S. G.; Ahmad, H. (Mol. Diversity, 2022)

(untitled) - Jung, N.; Bräse, S. (Eur. J. Org. Chem., 2009)

(untitled) - Busacca, C. A.; Fandrick, D. R.; Song, J. J.; Senanayake, C. H. (Adv. Synth. Catal., 2011)

(untitled) - Jeschke, P. (Eur. J. Org. Chem., 2022)

(untitled) - Gao, Y.; Feng, C.; Seo, T.; Kubota, K.; Ito, H. (Chem. Sci., 2022)

Electrophilic Aromatic Substitution - Taylor, R. (John Wiley & Sons, 1990)

(untitled) - Saikia, I.; Borah, A. J.; Phukan, P. (Chem. Rev., 2016)

(untitled) - Voskressensky, L. G.; Golantsov, N. E.; Maharramov, A. M. (Synthesis, 2016)

(untitled) - Muathen, H. A. (J. Org. Chem., 1992)

(untitled) - Majetich, G.; Hicks, R.; Reister, S. (J. Org. Chem., 1997)

(untitled) - Roy, S. C.; Guin, C.; Rana, K. K.; Maiti, G. (Tetrahedron Lett., 2001)

(untitled) - Naresh, M.; Kumar, M. A.; Reddy, M. M.; Swamy, P.; Nanubolu, J. B.; Narender, N. (Synthesis, 2013)

(untitled) - Li, X.-L.; Wu, W.; Fan, X.-H.; Yang, L.-M. (RSC Adv., 2013)

(untitled) - Krishna Mohan, K. V. V.; Narender, N.; Srinivasu, P.; Kulkarni, S. J.; Raghavan, K. V. (Synth. Commun., 2004)

(untitled) - Ross, S. D.; Finkelstein, M.; Petersen, R. C. (J. Am. Chem. Soc., 1958)

(untitled) - Mitchell, R. H.; Lai, Y.-H.; Williams, R. V. (J. Org. Chem., 1979)

(untitled) - Carreno, M. C.; Garcia Ruano, J. L.; Sanz, G.; Toledo, M. A.; Urbano, A. (J. Org. Chem., 1995)

(untitled) - Zysman-Colman, E.; Arias, K.; Siegel, J. S. (Can. J. Chem., 2009)

(untitled) - Pingali, S. R. K.; Madhav, M.; Jursic, B. S. (Tetrahedron Lett., 2010)

(untitled) - Pramanick, P. K.; Hou, Z.-L.; Yao, B. (Tetrahedron, 2017)

(untitled) - Bovonsombat, P.; Teecomegaet, P.; Kulvaranon, P.; Pandey, A.; Chobtumskul, K.; Tungsirisurp, S.; Sophanpanichkul, P.; Losuwanakul, S.; Soimaneewan, D.; Kanjanwongpaisan, P.; Siricharoensang, P.; Choosakoonkriang, S. (Tetrahedron, 2017)

(untitled) - Song, S.; Sun, X.; Li, X.; Yuan, Y.; Jiao, N. (Org. Lett., 2015)

(untitled) - Bovonsombat, P.; Ali, R.; Khan, C.; Leykajarakul, J.; Pla-on, K.; Aphimanchindakul, S.; Pungcharoenpong, N.; Timsuea, N.; Arunrat, A.; Punpongjareorn, N. (Tetrahedron, 2010)

(untitled) - Racys, D. T.; Sharif, S. A. I.; Pimlott, S. L.; Sutherland, A. (J. Org. Chem., 2016)

(untitled) - Mostafa, M. A. B.; Bowley, R. M.; Racys, D. T.; Henry, M. C.; Sutherland, A. (J. Org. Chem., 2017)

(untitled) - Nishii, Y.; Ikeda, M.; Hayashi, Y.; Kawauchi, S.; Miura, M. (J. Am. Chem. Soc., 2020)

(untitled) - Hirose, Y.; Yamazaki, M.; Nogata, M.; Nakamura, A.; Maegawa, T. (J. Org. Chem., 2019)

(untitled) - Xu, H.; Hu, L.; Zhu, G.; Zhu, Y.; Wang, Y.; Wu, Z.-G.; Zi, Y.; Huang, W. (RSC Adv., 2022)

(untitled) - Xu, X.; Luo, J. (ChemSusChem, 2019)

(untitled) - Bedford, R. B.; Haddow, M. F.; Mitchell, C. J.; Webster, R. L. (Angew. Chem., Int. Ed., 2011)

(untitled) - John, A.; Nicholas, K. M. (J. Org. Chem., 2012)

(untitled) - Sun, X.; Sun, Y.; Zhang, C.; Rao, Y. (Chem. Commun., 2014)

(untitled) - Schröder, N.; Wencel-Delord, J.; Glorius, F. (J. Am. Chem. Soc., 2012)

(untitled) - Bhardwaj, N.; Singh, A. K.; Tripathi, N.; Goel, B.; Indra, A.; Jain, S. K. (New J. Chem., 2021)

(untitled) - Tang, R.-J.; Milcent, T.; Crousse, B. (J. Org. Chem., 2018)

(untitled) - Friščić, T.; Mottillo, C.; Titi, H. M. (Angew. Chem., Int. Ed., 2020)

Ball milling towards green synthesis: Applications, projects, challenges - Stolle, A.; Ranu, B. C. (Royal Society of Chemistry, 2014)

(untitled) - Gomollón-Bel, F. (Chem. Int., 2019)

(untitled) - Tanaka, K.; Toda, F. (Chem. Rev., 2000)

(untitled) - Banerjee, M.; Panjikar, P. C.; Das, D.; Iyer, S.; Bhosle, A. A.; Chatterjee, A. (Tetrahedron, 2022)

(untitled) - Das, D.; Bhutia, Z. T.; Panjikar, P. C.; Chatterjee, A.; Banerjee, M. (J. Heterocycl. Chem., 2020)

(untitled) - Bose, A.; Mal, P. (Tetrahedron Lett., 2014)

(untitled) - Ghanbari, N.; Ghafuri, H.; Zand, H. R. E.; Eslami, M. (SynOpen, 2017)

(untitled) - Liu, Z.; Xu, H.; Wang, G.-W. (Beilstein J. Org. Chem., 2018)

(untitled) - Bhutia, Z. T.; Prasannakumar, G.; Das, A.; Biswas, M.; Chatterjee, A.; Banerjee, M. (ChemistrySelect, 2017)

(untitled) - Banerjee, M.; Chatterjee, A.; Kumar, V.; Bhutia, Z. T.; Khandare, D. G.; Majik, M. S.; Roy, B. G. (RSC Adv., 2014)

(untitled) - Das, D.; Bhutia, Z. T.; Chatterjee, A.; Banerjee, M. (J. Org. Chem., 2019)

(untitled) - Declerck, V.; Colacino, E.; Bantreil, X.; Martinez, J.; Lamaty, F. (Chem. Commun., 2012)

(untitled) - Varenikov, A.; Shapiro, E.; Gandelman, M. (Chem. Rev., 2021)